Social support as a bridge: A rapid realist review of migrant inclusion in the Japanese response to the COVID-19 pandemic - Russell Miller; Kuniko Arita; Niaya Harper Igarashi; Daiki Fujii; Aya Yumino; Masamine Jimba (Elsevier, 2022)
Government policy to address the COVID-19 pandemic has been complex with profound impacts on vulnerable minorities like international migrants. In Japan migrants are an important and growing community but their consideration in health policy is rare. We conducted a rapid realist review about 'what works' for the equitable inclusion of migrants during the pandemic as a case study for other public health emergencies. Due to the time-sensitive needs of policy-makers in the ongoing COVID-19 emergency, our evidence search was purposive, yet exploratory and iterative in nature. We assessed academic and gray literature sources, published in either English or Japanese, that examined the policy response to COVID-19 in Japan and its impact on migrants. A panel of external stakeholders was also consulted during the review process. This evidence synthesis suggests that, rather than illness alone, restrictions on movement and socioeconomic background lead to the considerable impact of policy on the well-being of migrants. Many policy responses, while conceptually inclusive and flexible, were often structurally inequitable for migrants. Poor outcomes included confusion about changing virus-related regulations and need for technical assistance to access support. Social support from volunteers and non-profit organizations were consistently left to connect migrants with unmet needs to available services. Using the diverse international community of Japan as an example, we show that, during public health emergencies, social support from civil society remains crucial for bridging structural inequities. For equitable inclusion of migrants, evidence-informed policy will be key for governments to better protect migrants' right to health and well-being in future emergencies.